Impact of human-associated Escherichia coli clonal groups in Antarctic pinnipeds: presence of ST73, ST95, ST141 and ST131 - Mora, Azucena; García-Peña, Francisco Javier; Alonso, María Pilar; Pedraza-Diaz, Susana; Ortega-Mora, Luis Miguel; Garcia-Parraga, Daniel; López, Cecilia; Viso, Susana; Dahbi, Ghizlane; Marzoa, Juan; Sergeant, Martin J.; García, Vanesa; et al. (Scientific reports, 2018)
There is growing concern about the spreading of human microorganisms in relatively untouched ecosystems such as the Antarctic region. For this reason, three pinniped species ( Leptonychotes weddellii , Mirounga leonina and Arctocephalus gazella ) from the west coast of the Antartic Peninsula were analysed for the presence of Escherichia spp. with the recovery of 158 E . coli and three E . albertii isolates. From those, 23 harboured different eae variants (α1, β1, β2, ε1, θ1, κ, ο), including a bfpA -positive isolate (O49:H10-A-ST206, eae -k) classified as typical enteropathogenic E . coli . Noteworthy, 62 of the 158 E . coli isolates (39.2%) exhibited the ExPEC status and 27 (17.1%) belonged to sequence types (ST) frequently occurring among urinary/bacteremia ExPEC clones: ST12, ST73, ST95, ST131 and ST141. We found similarities >85% within the PFGE-macrorrestriction profiles of pinniped and human clinic O2:H6-B2-ST141 and O16:H5/O25b:H4-B2-ST131 isolates. The in silico analysis of ST131 Cplx genomes from the three pinnipeds (five O25:H4-ST131/PST43- fimH 22-virotype D; one O16:H5-ST131/PST506- fimH 41; one O25:H4-ST6252/PST9- fimH 22-virotype D1) identified IncF and IncI1 plasmids and revealed high core-genome similarities between pinniped and human isolates ( H 22 and H 41 subclones). This is the first study to demonstrate the worrisome presence of human-associated E . coli clonal groups, including ST131, in Antarctic pinnipeds.